The Food System in the (Post-)Pandemic World: Disruptions, Vulnerability, Resilience, and Alternatives - 1 - Bjørkhaug, Hilde; Büke, Atakan; Ribeiro, José Duarte; Sippel, Sarah Ruth (The International Journal of Sociology of Agriculture and Food, 2023)
COVID-19 sharply exposed the vulnerabilities of capitalist-industrial agri-food relations and significantly intensified them. At the same time, we have also seen that agri-food relations can be resilient, that some systems prospered when changes were needed, and that many people experienced new forms of solidarity. This is the first of the two special sections to be published successively in the International Journal of Sociology of Agriculture and Food (IJSAF). We aim to revisit the major themes of the sociology of agriculture and food, specifically focusing on what the COVID-19 pandemic has revealed about them: the globalisation of agri-food, the reconfiguration of socio-ecological linkages between agri-food and nature, the politics of agriculture and food, and the methodological and theoretical ways we make sense of these within agri-food scholarship. This introduction presents the background of the special section and the underlying motives for bringing together the empirical articles.